Mengelola Efektivitas Organisasi Pesantren: Model Kesesuaian Budaya Organisasi - Muhammad Anggung Manumanoso Prasetyo; Agus Salim Salabi; Akhmad Muadin (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2021)
This research aims to understand the strategic role of boarding school culture in improving organizational effectiveness. It is hypothesized that boarding school cultures affect the organization's effectiveness. This writing uses a mixed-method research design consisting of extensive empirical surveys followed by semi-structured and focused group interviews and relevant document checks. The data reported are based on an empirical survey involving six boarding school leaderships in Southeast Aceh County followed by interviews and focused group discussions with all related stakeholders. The possibility of general application of the findings is limited by the organization's scope, sample, and cultural context of the study. The application of the oldest strategy in the organization's cultural elements are the value of independence, the value of development, and the value of regeneration. The findings suggest that when the boarding school culture is developed effectively, it will shape positive behaviors that collectively impact boarding school organizations' increased effectiveness. Effective boarders were able to create a fundamental order for Aceh society because it managed to keep existing cultural values. The personification is traditionally inherited through the teacher's relationship to his saints in the building of the system that is formed and can be seen from the values of existing boarding school culture.